Interaction Between Interferon Regulatory Factor-1 and Human Papillomavirus E7 Oncogene in Cervical Cancer: An Ontology Study - Viroj Wiwanitkit (Elsevier, 2009)
Objective: Cervical cancer is an important female malignancy. The discovery of human papillomavirus (HPV) as an etiologic agent of cervical cancer has prompted increased interest in the biology and oncogenicity of this virus. The E7 protein is found predominantly in the nucleus and, to a lesser extent, in the cytoplasm in cervical cancer cell lines. HPV E7 has been shown to be functionally associated with the tumor suppressor interferon regulatory factor (IRF)-1 in cervical carcinogenesis. Materials and Methods: In this study, new gene ontology technology was used to predict changes in the molecular function and biologic processes caused by the interaction between IRF-1 and HPV E7. Results: The molecular function and biologic processes of IRF-1 and the combined IRF-1 and HPV E7 (IRF-1-E7) were derived using the GoFigure server. The combined IRF-1-E7 demonstrated more functions and biologic processes compared with IRF-1 alone. Conclusion: IRF-1-E7 was shown to be responsible for the positive regulation of many interleukins and to be involved in the differentiation of T-helper cells.